Living arrangements, health outcomes, and the buffering role of social capital among older adults in China - Zheng, Jichao; Ni, Zeqiang (Frontiers in Public Health, 2025)
BackgroundCurrently, about 40 million older people in China live alone or in nursing homes, and this number is expected to continue increasing. It is important to examine the effects of living arrangements on older people’s health status and determine whether different types of social capital help buffer the health effects of living alone or in nursing homes.MethodWe used data from the CLHLS survey (2017–2018), which included 9,669 older adults. Among them, 1,542 lived alone, 312 lived in nursing homes, and 7,815 lived with their family. We used linear regression to examine the relationship between living arrangements, health outcomes, and social capital.ResultsLiving alone leads to higher levels of depression in older adults, with a coefficient of 1.63 for the depression value for older adults, and living alone reduces older adults’ self-rated health scores, with a coefficient of −0.12 on the self-rated health scores for older adults. Living in nursing homes also has a significant effect on the mental health of older adults, with a coefficient of 1.31 for the depression value for older adults. At the same time, we find that different categories of social capital buffer the impact of living alone and living in nursing homes on health. We find that visits from children helped mitigate the increase in depression associated with living in nursing homes and the decrease in self-rated health associated with living alone. At the same time, social interactions at the community level help mitigate the increase in depression values and the reduction of self-rated health scores associated with living alone.ConclusionDifferent categories of social capital buffer the health of older people living alone and in nursing homes differently, so targeted enhancement of social capital based on older adults’ living arrangements is essential to improve their health.